What drives carbon emissions in German manufacturing: Scale, technique or composition? - Elisa Rottner; Kathrine von Graevenitz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Drastic emission reductions are necessary to combat climate change. However, despite several climate policies, carbon emissions from German manufacturing have actually increased between 2005 and 2017. In this paper, we provide evidence of how the policy mix overall has affected the German manufacturing sector in its entirety. Using detailed administrative micro-data at the product-level, we decompose changes in carbon emissions between 2005 and 2017 into scale, composition (changes in the mix of goods produced) and technology (emission factors of production) effects. We find that much of the increase in carbon emissions is due to an increase in manufacturing's production scale. Relative to the strong output growth, our analysis reveals a clean-up of manufacturing of 9 %. This clean-up is exclusively due to a shift towards a cleaner product composition from 2011 onwards, while production technique has mostly become dirtier. The results display substantial sectoral heterogeneity and are largely driven by the most energy and emission intensive sectors.
Keywords: D22; L60; Q41; Q48; 330; Carbon emissions; Climate Policy; Statistical Decomposition; Manufacturing